Observational study to estimate the proportion of surgical site infection following excision of ulcerated skin tumours (OASIS study). (30th December 2021) - Abbott, R. A.; Cordaro, A.; Lloyd, B.; Cannings‐John, R.; Wootton, M.; Kirby, N; Pickles, T.; McQueen, A.; Westmoreland, M.; Ziaj, S.; Martin‐Clavijo, A.; Wernham, A.; et al.
Summary: Background: Ulceration is a recognized risk factor for surgical site infection (SSI); however, the proportion of patients developing SSI after excision of an ulcerated skin cancer is unknown. Aim: To determine the proportion of participants with SSI after surgical excision of an ulcerated skin cancer. A secondary aim was to assess feasibility outcomes to inform the design of a randomized controlled trial to investigate the benefits and harms of perioperative antibiotics following excision of ulcerated tumours. Methods: This was a multicentre, prospective, observational study of patients undergoing excision of an ulcerated skin cancer between March 2019 and March 2020. Prior to surgical excision, surface swabs of the ulcerated tumours of participants recruited from one centre were undertaken to determine organism growth. At 4 weeks after surgery, all participants were e‐mailed or posted the Wound Healing Questionnaire (WHQ) to determine whether they had developed SSI. Results: In total, 148 participants were recruited 105 (70.9%) males; mean ± SD age 77.1 ± 12.3 years. Primary outcome data were available for 116 (78.4%) participants, of whom 35 (30.2%) were identified as having an SSI using the WHQ with a cutoff score of 8, and 47 (40.5%) were identified with a cutoff score of 6. Using the modified WHQ in participants with wounds left to heal by secondary intention, 33 (28.4%) and 43 (37.1%) were identified to have SSI respectively. Conclusion: This prospective evaluation of SSI identified with the WHQ following excision of ulcerated skin cancers demonstrated a high proportion with SSI. The WHQ was acceptable to patients; however, further evaluation is required to ensure validity in assessing skin wounds. Abstract : We undertook a multicentre, prospective, observational study of patients undergoing excision of an ulcerated skin cancer to determine the proportion of participants with surgical site infection (SSI). Four weeks after surgery, all participants were e‐mailed or posted the Wound Healing Questionnaire (WHQ) to determine whether they had developed SSI. Primary outcome data were available for 116 (78.4%) participants, of whom 35 (30.2%) were identified to have SSI using the WHQ with a cutoff score of 8, and 47 (40.5%) were identified with a cutoff score of 6.